(3TQM CQLhRI aj eKdKGJ bWQHs - (3eLghds; (3CHj Ydj Hf CMeO Hf GdeSJfjQ, bWQH,J (B206 (3g` s
(3ChdgG (B:s
(3jG ehdYkG HGdZVH hGdgLQ hGdJLfH MHc bO HQM Hi Qai LOg hGddYH s
(3BNQgG (B:s
(3deG QCjJ Odg hgLQg heWdg fXeJ ai MHi dg eKdKkG dbWQH hGdMeO ddg OGFekG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs